The Effect of ESG and Financial Constraints on Cost of Equity: Institutional Ownership as a Moderating Variable - Desak Putu Arde Suari; Gede Adi Yuniarta; Lucy Sri Musmini (LifeSciFi, 2026)
Environmental, Social, and Governance (ESG) disclosure and financial constraints influence investors’ risk perceptions and the cost of equity, yet the moderating role of institutional ownership remains inconclusive. This study examines the effects of ESG disclosure and financial constraints on the cost of equity, as well as the moderating role of institutional ownership, among non-primary consumer companies listed on the Indonesia Stock Exchange. A quantitative approach was employed using balanced panel data from 63 companies during 2022–2024 (189 firm-year observations). The study employed the CAPM, ESGDI, SA Index, and institutional ownership ratio to measure the variables. The data were analyzed using random-effects panel regression with robust standard errors clustered and the firm level and moderated regression analysis in Stata. The results show that ESG disclosure significantly reduces the cost of equity, whereas financial constraints significantly increase it. However, institutional ownership does not significantly moderate the effects of ESG disclosure or financial constraints on the cost of equity. These findings suggest that investors place greater emphasis on sustainability disclosure and firms’ financial conditions than on ownership structure when evaluating investment risk. The study provides evidence that strengthening ESG disclosure and maintaining financial flexibility are effective strategies for reducing equity financing costs in emerging markets.